Lobbying Conflict, Competition, and Working in Coalitions. (22nd April 2019) - Newmark, Adam J.; Nownes, Anthony J.
Abstract : Objective: We examine the factors that affect interest group decisions to join coalitions rather than "go it alone." Among the factors we consider are organization type, level of conflict, level of competition, and relative influence. Method: We conduct a mail survey of lobbyists in five American states to determine the likelihood of interests working in coalitions. Results: Our findings indicate that group type has little impact on group decisions to join coalitions. Advantaged (e.g., resource‐rich business organizations) and disadvantaged (e.g., underfunded charity and citizen groups) groups behave similarly when it comes to working with others, a finding that is important in debates over whether some interests are over‐ or underrepresented in the pressure system. We also find that conflict and competition affect groups' propensity to work with other groups, and that contextual factors, including partisan congruence and lobbying laws, influence the extent to which groups work with other groups. Conclusion: Our findings contribute to the ongoing scholarly debate about the conditions under which interest groups bear the costs of lobbying with others.